Determination of Oxidative Stress Related Toxicity on Repeated Dermal Exposure of Hydroxyapatite Nanoparticles in Rats - Parayanthala Valappil, Mohanan; Santhakumar, Syama; Arumugam, Sabareeswaran (International Journal of Biomaterials, 2014)
Hydroxyapatite nanoparticles (HANPs) have numerous applications, such as substitute for bone grafting, bone fillers, bioceramic coating, and dental fillings. The toxicity of these nanomaterials is of growing concern despite their significant scientific interest and promising potential in many applications. In this study, an in-house synthesized, characterized HANP of size <50 nm was investigated for the dermal toxicity. A paste of HANPs was prepared in water and applied on the dorsal side of the rats for 28 days. At the end of 28 days, blood was subjected to haematological and biochemical analysis. Gross necropsy was conducted and major organs were collected for histopathological observations. Liver from the animals was evaluated for lipid peroxidation, reduced glutathione, and antioxidant enzymes activity. It was observed that none of the animals showed any abnormality during the experimental period. Gross examination of carcasses did not reveal any abnormality in the organs examined. The results also demonstrated that there was no significant fluctuation in the level of antioxidant defense mechanisms, lipid peroxidation, and haematological and biochemical parameters. There was no histopathological lesion observed in any of the organs. Hence, it can be concluded that the synthesized HANPs were nontoxic at cellular level, when exposed dermally to rats.